Consider the given quadratic equation,
![x^2+x=(19)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/7pn88dywn397n6zdghrpc0yaypxs9figyt.png)
Here the coefficient of 'x' is positive, so the algebraic identity which will be used in the method of completing squares, is as follows,
![a^2+2ab+b^2=\mleft(a+b\mright)^2](https://img.qammunity.org/2023/formulas/mathematics/college/doj8gt0ongk7j0xbfq63izgjs4q3kkjca0.png)
Writing the left side of the given equation in the form of the left side expression of the identity,
![(x)^2+2(x)((1)/(2))=(19)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/o7xiymuiyn392tcyydtwyqa5xh8j19s00v.png)
It is observed that,
![\begin{gathered} a=x \\ b=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bwi947tyjpkj6mk0arrxlanbq9h557of3v.png)
Note that, in order to complete the square, the left side expression requires a 'b-squared' term.
This can be done by adding the term to both sides of the equality.
Adding the term both sides,
![\begin{gathered} (x)^2+2(x)((1)/(2))+((1)/(2))^2=(19)/(4)+((1)/(2))^2 \\ (x)^2+2(x)((1)/(2))+((1)/(2))^2=(19)/(4)+((1)/(4))^{} \\ (x)^2+2(x)((1)/(2))+((1)/(2))^2=(19+1)/(4) \\ (x)^2+2(x)((1)/(2))+((1)/(2))^2=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/511vck4gcq71fe13k20lzbivwgboxga7ks.png)
Now, the left side of the expression perfectly fits the left side expression of the algebraic identity, which can be replaced by its right side term,
![(x+(1)/(2))^2=5](https://img.qammunity.org/2023/formulas/mathematics/college/kqywvn4jolpxkcja6q77z2af0it6niwo1i.png)
Taking square rootsboth sides,
![\begin{gathered} x+(1)/(2)=\pm\sqrt[]{5} \\ x+(1)/(2)=\sqrt[]{5}\text{ }or\text{ }x+(1)/(2)=-\sqrt[]{5}\text{ } \\ x=\sqrt[]{5}-(1)/(2)or\text{ }x=-\sqrt[]{5}-(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ah5uiqox8h7wa6g2qmprj2olr6deqyym6r.png)
Thus, the solutions of the given quadratic equations are,
![x=\sqrt[]{5}-(1)/(2)or\text{ }x=-\sqrt[]{5}-(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/4z9x2sj0mzwbpgbe0hjz4zyo006bc2k0ag.png)
Therefore, option C is the correct choice.